Social Media and Communication Literacy: Exploring the Relationship between Usage Intensity among Education Administration Students - Novriyanti Achyar; Anisah Anisah; Sari Febrianti; Singgih Ginanjar (Journal of Current Studies in SDGs, 2027)
Abstract. This study aims to examine the influence of social media usage intensity on communication literacy skills among students majoring in Educational Administration. The method used in this research is a quantitative approach with survey techniques. The research sample consisted of 121 students randomly selected from 623 registered students in the Department of Educational Administration at Padang State University. Data was collected through a questionnaire that measures the intensity of social media use and media literacy skills in student communication. Data analysis using the Pearson correlation method to identify the relationship between the two variables. The research results show a significant positive correlation between the intensity of social media use and the communication literacy skills of students. Students who have a relatively high intensity of social media use tend to have better communication literacy. Based on Pearson's correlation analysis, the obtained correlation value is 0.442 with a significance of 0.003. This result shows that social media can be an effective tool in improving communication skills if used wisely. This research suggests that the use of social media in the educational context should be better considered to support the development of students' communication literacy skills.